2007
DOI: 10.1007/s00535-007-2011-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of reflux esophagitis following esophagectomy with gastric tube reconstruction

Abstract: To detect the presence of RE as well as monitor for recurrence and development of metachronous cancer, we consider it important to perform endoscopy regularly over the long term. As Barrett's epithelium is frequently encountered, care should be exercised to detect the specialized columnar epithelium showing dysplastic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 12 publications
3
36
0
Order By: Relevance
“…Thus, we cannot say with certainty that the enlarged proximal gastrectomy contributed to the reduction of esophagitis and Barrett in our patients. Other authors also found the occurrence of esophagitis and Barrett's esophagus in the esophageal stump of patients with gastric tube, since its vertical position is maintained, facilitating rapid gastric emptying, as well as duodenogastric reflux 34,35,38,39 . We conducted esophagectomy with enlarged proximal gastrectomy (gastric tube) and yearly endoscopy, as experts recommend.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, we cannot say with certainty that the enlarged proximal gastrectomy contributed to the reduction of esophagitis and Barrett in our patients. Other authors also found the occurrence of esophagitis and Barrett's esophagus in the esophageal stump of patients with gastric tube, since its vertical position is maintained, facilitating rapid gastric emptying, as well as duodenogastric reflux 34,35,38,39 . We conducted esophagectomy with enlarged proximal gastrectomy (gastric tube) and yearly endoscopy, as experts recommend.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 93%
“…Considering that in these patients, basal and stimulated acid secretion is lower than that found in normal subjects, and the right colon may be affected by the disease, reconstitution with the stomach initially appeared to be a great option. However, the follow-up of patients submitted to esophagectomy with this type of reconstitution and without the use of proton pump inhibitor (PPI) may show disastrous complications, such as Barrett's esophagus and esophageal stump cancer 25,[33][34][35] .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPIs were also introduced to all patients during the first week after surgery in our hospital because of increased risk for prolonged esophageal exposure to gastric acid and duodenal juice. It was confirmed useful for the treatment of RE as most patients showed endoscopic improvement in the severity of the reflux after treatment (9). However, we do not encourage the long-term use of PPIs because of its negative effect on the digestive system and the relatively lower incidence of RE in Asia (19).…”
Section: Discussionmentioning
confidence: 99%
“…Using the Los Angels classification ( Table 1), Shibuya observed sever esophagitis (grade C or D) in 75% o f their patients [17]. In another series of 48 patients , Yamamoto [18] found reflu x esophagitis in 27 o f their 48 patients (56.3%) and majority (70%) had a Los Angeles C or D damage.…”
Section: Reflux Esophagitismentioning
confidence: 97%